EDITORIAL NOTE - Perrotini Hernández, Ignacio (Investigación Económica, 2018)
Investigación Económica (Economic Research), the School of Economics of UNAM’s emblematic Journal, has been published quarterly and steadfastly since 1941, when Mr Jesús Silva Herzog founded it, while both Mexico and the world economy were faced with challenging crossroads. Ever since, Investigación Económica has been a sedulous outlet for cutting-edge scholarly papers by both Mexican and foreign economists examining —from different analytical and paradigmatic perspectives, though rigorously ingrained on state-of-the-art methodology and axiomatic economic principles— the most pressing issues of economic theory and policy alike. I had the privilege of looking after the journal as chief editor during 2006-2012. In those years, Investigación Económica strengthened, became a bilingual (Spanish-English) journal, adopted the best editorial practices worldwide, was indexed in the top lists of scholarly journals, both at national and international levels, and was also invited to join JSTOR. As a result of the collective editorial work of that period, Investigación Económica was ranked as the best Mexican economic journal, hence its higher impact factor reached years later. I am honoured to take over the editorship of the journal once again, and bound to bear in mind such rich plural history, free of dogmatism. The current defiance, as it were, lies in going À la recherche du temps perdu, to quote Marcel Proust. Alas, the task is superlative in various ways. For Investigación Económica must contribute to defy and defeat the pernicious influence of the dogmatic TINA (there-is-no-alternative) way of thinking and dealing with economic phenomena that became so pervasive worldwide over the last decades. After all, it was Adam Smith who remarked that “science is the great antidote of the poison of enthusiasm and superstition.” Indeed, since economics is a moral science, there is no such thing as a unique absolute truth, free of value judgements, as Gunnar Myrdal put it. Paraphrasing Adam Smith, on the road from the City of Skepticism, one has to pass through the Valley of Ambiguity. Furthermore, Mexico, the world economy and even the science of economics are currently “passing through a valley” full of amphibology and riddles. Fortunately, a renewed editorial board (EB), composed of highly regarded colleagues, will help me cope with the difficult duty. We gratefully thank those colleagues who, due to the rules of the EB, now regretfully leave it; needless to say, their priceless contribution enhanced the journal’s quality. Likewise, the newcomers, who in all probability shall help us move forward, are most welcome. Investigación Económica is a public good, representing a forum for conversation and discussion of competing ideas —beyond ideological prejudices— for both the general well-being and the progress of the economic discipline, particularly in today’s world plagued by theoretical paradoxes, pragmatic pressing needs and expectations of positive change. Therefore, the scientific community is called upon to submit high calibre research papers aimed at contributing to feasible solutions to the problems facing economics and the economy at large.